The Creep Model of the Anchorage Structure and the Time-Dependent Reliability Analysis - Wang, Jun; Liang, Qiao; Duan, Jian (Frontiers in Earth Science, 2020)
The anchorage structure is a complex bearing system with undetermined failure modes. According to component characteristics, the segmented diagram for the bearing characteristics and the bearing structure at the anchorage segment were established. In addition, we described the failure patterns of the subsystems of the anchorage structure and further established the series model for the reinforced system by bolts. Moreover, according to the total displacement and the time-dependent deformation characteristics of the bolt, a non-linear creep model to analyze the viscoplastic deformation characteristics of the M-C element was established. Furthermore, considering the shear strength of the anchored soil, it was assumed that the cohesion and the internal friction angle were random variables following the Weibull distribution. Using the modified first-order second-moment method (the JC method), the analytic expression of the time-dependent index of the anchorage system was obtained. An example showed that the variable coefficients of the cohesion and the internal friction angle were exponentially and linearly related to the reliability index, respectively. Simultaneously, the reliability index was exponentially related to time.